Studies of J/[psi] production at forward rapidity in Pb-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Leardini, Lucia; Pachmayer, Yvonne C.; Reygers, Klaus; et al. (Journal of high energy physics, 2020)
The inclusive J/ψ production in Pb-Pb collisions at the center-of-mass energy per nucleon pair sNN$$ \sqrt{s_{NN}} $$ = 5.02 TeV, measured with the ALICE detector at the CERN LHC, is reported. The J/ψ meson is reconstructed via the dimuon decay channel at forward rapidity (2.5 < y < 4) down to zero transverse momentum. The suppression of the J/ψ yield in Pb-Pb collisions with respect to binary-scaled pp collisions is quantified by the nuclear modification factor (RAA). The RAA at sNN$$ \sqrt{s_{NN}} $$ = 5.02 TeV is presented and compared with previous measurements at sNN$$ \sqrt{s_{NN}} $$ = 2.76 TeV as a function of the centrality of the collision, and of the J/ψ transverse momentum and rapidity. The inclusive J/ψ RAA shows a suppression increasing toward higher transverse momentum, with a steeper dependence for central collisions. The modification of the J/ψ average transverse momentum and average squared transverse momentum is also studied. Comparisons with the results of models based on a transport equation and on statistical hadronization are carried out.
ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, M. Danisch, V. Feuillard, P. Glässel, J. Kim, M. Kim, M.K. Köhler, L. Leardini, Y.C. Pachmayer, K. Reygers, R. Schicker, A. Schmah, M.O. Schmidt, J. Stachel, B. Windelband [und viele weitere]
Im Titel ist "psi" als griechischer Buchstabe dargestellt
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Gesehen am 07.04.2020